2010
DOI: 10.1089/chi.2010.0419
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Mothers' and Their Children's Weights at 4 Years of Age

Abstract: Objectives To examine the importance of maternal weight characteristics as predictors of overweight (BMI ≥85th percentile and <95th percentile) and obesity (BMI ≥ 95th percentile) in offspring at age 4 years. Methods Chi-square and logistic regression analyses were conducted on a sample of 321 mother/child pairs from an earlier observational cohort study on mothers’ postpartum weight retention. Results Maternal early pregnancy BMI and infant birth weight were each positively and significantly (p <0.05) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 17 publications
4
38
0
2
Order By: Relevance
“…This finding suggests that healthy post-pregnancy weight may join normal prepregnancy BMI and adequate GWG as potentially modifiable risk factor for child overweight and obesity. Our data also reinforce that prepregnancy BMI (Li et al, 2005; Olson et al, 2010; Weden et al, 2012; Whitaker, 2004) and GWG (IOM, 2009; Nehring et al, 2013) are each independently associated with child overweight. The association between both GWG and PDWC with child overweight appeared driven by overweight and obese mothers.…”
Section: Discussionsupporting
confidence: 81%
“…This finding suggests that healthy post-pregnancy weight may join normal prepregnancy BMI and adequate GWG as potentially modifiable risk factor for child overweight and obesity. Our data also reinforce that prepregnancy BMI (Li et al, 2005; Olson et al, 2010; Weden et al, 2012; Whitaker, 2004) and GWG (IOM, 2009; Nehring et al, 2013) are each independently associated with child overweight. The association between both GWG and PDWC with child overweight appeared driven by overweight and obese mothers.…”
Section: Discussionsupporting
confidence: 81%
“…These results supported previous studies. A US study reported that 36% of children (3.5 to 4.5 years) of obese mothers were obese, whereas only 7.8% of children of mothers with normal weight were obese [31]. Previous studies have found that offspring born to mothers with excessive GWG or higher prepregnancy BMI were associated with an increased risk of overweight and obesity from childhood to adulthood [32-34].…”
Section: Discussionmentioning
confidence: 99%
“…Regression coefficients, ORs and CIs are reported in the tables. We adjusted 4-year multivariable models for sex, race, SES, juice and SSB intake,14 number of glasses of milk daily and maternal BMI 15. For juice, SSB and milk intake, we used the amount of each of these reported by the parents as the number of daily servings with one to three times weekly=0.29 servings/day and four to six times weekly=0.71 servings/day.…”
Section: Methodsmentioning
confidence: 99%